2021
DOI: 10.3390/ani11051251
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Beneficial Changes to Racehorse Veterinary Care Implemented during the COVID-19 Pandemic

Abstract: In March 2020, the World Health Organisation called for countries to take urgent and aggressive action against a global pandemic caused by COVID-19. Restrictions were introduced in many countries to reduce transmission of COVID-19 and ultimately deaths. Such restrictions have been colloquially referred to as “lockdown”. Anecdotal evidence of the beneficial practices that facilitated safe veterinary treatment and equine care had been reported together with an increase in the use of electronic communication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The results from the present study conform with that of Butler et al [ 15 ], who noted that the majority of an equine veterinarian sample found teleconsultation to be excessively time consuming, preferring to physically assess cases, although, some found that consultations took less time; consistent with findings of Bishop et al [ 19 ]. A possible contributor to strained communication over telephone could be the loss of subtle interactions which normally punctuate person to person communication.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results from the present study conform with that of Butler et al [ 15 ], who noted that the majority of an equine veterinarian sample found teleconsultation to be excessively time consuming, preferring to physically assess cases, although, some found that consultations took less time; consistent with findings of Bishop et al [ 19 ]. A possible contributor to strained communication over telephone could be the loss of subtle interactions which normally punctuate person to person communication.…”
Section: Discussionsupporting
confidence: 91%
“…Focused evaluations on the impact of the pandemic upon distinct social cohorts can offer insights into the ways that social isolation, contagion and restricted living interact with sense of overall wellbeing within a community. Equestrian industry stakeholders form one such group which has received considerable attention from researchers seeking to understand the full impact of the pandemic upon human and animal welfare [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examining these challenges from the three domains above (PWDs, reduced social services and assistance, and adaptive veterinary service) further indicates complicities and interconnections. Research deficits associated with these complicities and interconnections reveal a comprehensive understanding of pandemic-related impacts to veterinary service access in PWDs [ 53 ]. Furthermore, the research will contribute to in-depth, evidence-based knowledge of this marginalized population’s experiences of owning animals during the pandemic.…”
Section: Pwds and Access To Veterinary Services During The Covid-19 Pandemicmentioning
confidence: 99%
“…Of the six cross-sectional studies, one was exclusively qualitative (Butler et al, 2021), and the rest were quantitative or a combination of both. Together they provided a comprehensive overview of their participants' outlook towards teleconsultation.…”
Section: The Evidencementioning
confidence: 99%
“…Arguments for its use is especially strong for that of remote locations, or in consults such as behavioural medicine when specialists are limited.The main issue with the body of evidence reviewed is the subjectivity of measuring satisfaction. The lack of clear definitions of subjectivity and approaches of measuring it, led to each study using different methods which varied greatly (e.g., the outcomes of a semi-structured interview (such asButler et al, 2021) are very different to a semi-quantified questionnaire (such as Magalhães-Sant'Ana et al, 2020). Even within one format such as a questionnaire, different authors asked differently phrased questions, and used subjective nonstandardised terms like 'excellent', 'good', 'poor' to calculate semi-quantitative scores.…”
mentioning
confidence: 99%